ANALISIS STRATEGI PENYELESAIAN PROGRAM LINIER MELALUI PENDEKATAN MODEL MATEMATIKA - Nuraini, Anggun; Octarina, Sisca; Puspita, Fitri Maya; Yuliza, Evi (Uninus Journal of Mathematics Education and Science (UJMES), 2026)
Mathematical modeling plays an essential role in mathematics learning, particularly in developing students analytical and problem-solving skills. Linear programming, as one of the core topics in optimization, often presents conceptual difficulties for students when linking abstract mathematical formulations to real-world problems. This study aims to analyze learning strategies for teaching linear programming through the implementation of mathematical modeling to improve students conceptual understanding and reasoning abilities. A descriptive qualitative approach was employed, focusing on literature review and classroom observations related to the used of mathematical models in teaching linear programming. The findings show that incorporating modeling steps-such as problem identification, variable formulation, and interpretation of result-helps students comprehend abstract mathematical ideas more effectively. Moreover, the integration of mathematical modeling encourages active learning and promotes students engagement in solving contextual problems. In conclusion, the use of mathematical modeling as a learning strategy provides a meaningful framework that enhances understanding, crirical thinking, and problem-solving skills in linear programming instruction.